PHYSICO-CHEMICAL PHENOMENA IN SOIL STABILIZATION FOR ROADS OR HIGHWAYS INFRASTRUCTURES - Anghel STANCIU; Anca HOTINEANU; Irina LUNGU (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2013)
Reducing the impact on the environment of constructing transportation infrastructures can be achieved through reusing or recycling certain materials. In this context, the current trend is to use materials that do not have a negative impact on the environment and provide a long term solution. Such local materials for the construction of transportation infrastructure are the active clays. This paper presents the physicochemical and mineralogical structure of clays and their behavior regarding the interaction with water. A negative effect of this interaction is the swelling, the contraction and, respectively, the swell pressure. These produce effects (fissures, cracks) in the structure of roads, highways and, respectively, airport runways. The authors analyze the possibility to reduce these effects by clay stabilization with mineral binders (cement, lime). Results on lime mixtures testing are presented in terms of physical and mechanical properties, and optimum percentages of the mixtures are presented. It is also concluded that this solution is more cost-effective than the classical one as replacing the clay layer from the roadbed with other filling materials transported from other areas.